The features of the global GAM in OH and ECRH plasmas in the T-10 tokamak. (30th April 2015) - Melnikov, A.V.; Eliseev, L.G.; Perfilov, S.V.; Lysenko, S.E.; Shurygin, R.V.; Zenin, V.N.; Grashin, S.A.; Krupnik, L.I.; Kozachek, A.S.; Solomatin, R.Yu.; Elfimov, A.G.; Smolyakov, A.I.; et al.
Abstract: Zonal flows and their high-frequency counterpart, the geodesic acoustic modes (GAMs) are considered as a possible mechanism of the plasma turbulence self-regulation. In the T-10 tokamak GAMs have been studied by the heavy ion beam probing and multipin Langmuir probes. The wide range of the regimes with Ohmic, on-axis and off-axis electron cyclotron resonance heating (ECRH) were studied ( B t  = 1.5–2.4 T, I p  = 140–300 kA, , P EC  < 1.2 MW). It was shown that GAM has radially homogeneous structure and poloidal m  = 0 for potential perturbations. The local theory predicts that, that means the frequency increases with the decrease of the minor radius. In contrast, the radial distribution of experimental frequency of the plasma potential and density oscillations, associated to GAM, is almost uniform over the whole plasma radius, suggesting the features of the nonlocal (global) eigenmodes. The GAM amplitude in the plasma potential also tends to be uniform along the radius. GAMs are more pronounced during ECRH, when the typical frequencies are seen in the narrow band from 22 to 27 kHz for the main peak and 25–30 kHz for the higher frequency satellite. GAM characteristics and the range of GAM existence are presented as functions of T e, density, magnetic field and P EC .